FePc / NiFe-LDH coated CB composite material and zinc air battery
The preparation of FePc/NiFe-LDH@CB composite material by room temperature synthesis method solves the complex problem of the catalyst synthesis method of traditional zinc air battery, achieves improvement of catalytic performance and reduction of production costs, and improves the market competitiveness of zinc air batteries.
Patent Information
- Application Number
- CN202411326245.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-07
AI Technical Summary
The catalyst synthesis method of traditional zinc air batteries is complex, increasing manufacturing costs and posing challenges to environmental friendliness. A simple and economical catalyst synthesis method is urgently needed.
The FePc/NiFe-LDH@CB composite material was prepared by room temperature synthesis method, and carbon black was used as the substrate to simplify the preparation process and maintain superior catalytic performance.
The catalytic performance is improved, production costs are reduced, and the market competitiveness of zinc air batteries is improved, showing excellent peak power density and good cycle stability.
Smart Images

Figure CN119400880A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of rechargeable zinc-air batteries, and the air cathode side specifically relates to the technical field of preparation of new energy materials. Background Art
[0002] With the development of renewable energy technology and the increasing demand for clean energy, zinc-air batteries, as a new type of energy storage device, have attracted widespread attention due to their high energy density, good safety and environmental friendliness. Zinc-air batteries use zinc sheets as negative electrode materials and oxygen in the air as positive electrode reactants to convert chemical energy into electrical energy during discharge. Compared with traditional lithium-ion batteries, zinc-air batteries have higher theoretical mass specific energy, which makes them have broad application prospects in electric vehicles, wearable devices and fixed energy storage systems.
[0003] At present, the research focus of zinc-air batteries is mainly on improving the activity and stability of their catalyst materials. The performance of the air cathode directly affects the overall performance of the battery, and studies have shown that transition metal hydroxide (such as NiFe-LDH)-based catalysts exhibit excellent catalytic performance in the oxygen evolution reaction. However, traditional oxygen reduction catalyst synthesis methods usually involve complex heat treatment processes, which not only increases manufacturing costs, but also challenges the environmental friendliness of the production process. Therefore, a simple and economical catalyst synthesis method is urgently needed to reduce the production cost of zinc-air batteries and improve their market competitiveness.
[0004] The FePc / NiFe-LDH@CB composite material proposed in the present invention adopts a room temperature synthesis method to prepare NiFe-LDH@CB, which greatly simplifies the preparation process while maintaining excellent catalytic performance. In addition, the carbon black used as a substrate in the present invention not only reduces the material cost, but also provides support for the conductivity and stability of the catalyst. By improving the catalytic activity of the air cathode and reducing the production cost, the present invention provides a new solution for the commercial application of zinc-air batteries. Summary of the invention
[0005] The present invention provides a FePc / NiFe-LDH@CB micro-nano composite material and a preparation method and application thereof. The material has high bifunctional activity and excellent tolerance, and the assembled liquid zinc-air battery has excellent peak power density and good cycle stability.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme: The specific steps include: S1: Preparation of NiFe-LDH@CB nanospheres: nickel salt and iron salt are added to an aqueous solution containing carbon black, and the mixture is aged in a mixed solution consisting of potassium hydroxide or sodium hydroxide aqueous solution, and then centrifuged, washed and dried to obtain NiFe-LDH@CB nanospheres; S2: Preparation of FePc / NiFe-LDH@CB composite material: NiFe-LDH@CB nanospheres were ultrasonically dispersed in DMF solution, and then FePc was dispersed in the solution, stirred overnight, and centrifuged, washed, and dried to obtain FePc / NiFe-LDH@CB composite material.
[0007] Furthermore, in step S1, the nickel salt is nickel nitrate, nickel chloride, nickel acetate, or nickel sulfate, and the concentration of the nickel salt in the aqueous solution is 0.15-0.3 g / L; the iron salt is iron nitrate, iron chloride, iron acetate, or iron sulfate, and the concentration of the iron salt in the aqueous solution is 0.05-0.1 g / L; the concentration of carbon black in the mixed solution is 2.5 g / L, and the added sodium hydroxide or potassium hydroxide is in excess.
[0008] Furthermore, in step S2: the NiFe-LDH@CB nanospheres are placed in a DMF solution and ultrasonically dispersed for 20-50 minutes.
[0009] Furthermore, in step S2: the concentration of FePc dispersed in the DMF solution is 0.5-0.8 g / L.
[0010] Furthermore, in the step S1-2: the entire process is carried out at room temperature.
[0011] The FePc / NiFe-LDH@CB micro-nano composite carbon material obtained by the above-mentioned preparation method has oxygen reduction performance and oxygen precipitation performance, and all preparation processes are carried out at room temperature without pyrolysis.
[0012] The present invention also provides a liquid zinc-air battery, which is assembled using FePc / NiFe-LDH@CB micro-nano composite carbon material as the air cathode side.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The FePc / NiFe-LDH@CB composite material of the present invention has excellent catalytic performance, with a half-wave potential of 0.925 V (vs. RHE) and a potential difference as low as 0.622 V, while also having excellent tolerance. By adopting a room temperature synthesis method, no pyrolysis process is required, which simplifies the preparation process of the catalyst and reduces the manufacturing cost. The FePc / NiFe-LDH@CB composite material exhibits an open circuit voltage of 1.45 V and a discharge peak power density of up to 202 mW / cm² in a zinc-air battery, and can be stably cycled for more than 2000 hours, showing excellent battery performance.
[0014] In addition, the environmental friendliness of the method meets the needs of sustainable development and has a wide range of application potentials. The preparation method of the FePc / NiFe-LDH@CB three-dimensional micro-nano composite air electrode of the present invention has the advantages of high repeatability, simple synthesis process, and easy control. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a SEM image of the carbon black substrate in Examples 1-3.
[0016] Figure 2 is a SEM image of the product prepared in Example 1.
[0017] Figure 3 is a SEM image of the product prepared in Example 2.
[0018] Figure 4 is a SEM image of the product prepared in Example 3.
[0019] Figure 5 is the XRD pattern of the product prepared in Example 1-3.
[0020] Figure 6 It is the Fourier transform infrared spectra of the product prepared in Example 1-3, carbon black and FePc.
[0021] Figure 7 Graph showing the ORR polarization curves of the ORR / OER bifunctional oxygen electrocatalysts prepared in Examples 1-3 of the present invention.
[0022] Figure 8 The ORR performance of the ORR / OER bifunctional oxygen electrocatalyst prepared in Example 3 of the present invention is compared with different FePc concentrations.
[0023] Fig. 9 Graph showing the OER polarization curves of the ORR / OER bifunctional oxygen electrocatalysts prepared in Examples 1-3 of the present invention.
[0024] Fig.10This is a performance diagram of the ORR stability test of the FePc / NiFe-LDH@CB micro-nano composite material and Pt / C+RuO2 prepared in Example 3.
[0025] Fig.11 This is a comparison of the LSV curves of the FePc / NiFe-LDH@CB micro-nanocomposite material prepared in Example 3 and Pt / C+RuO2 before and after the ORR stability test.
[0026] Fig.12 It is a comparison of the LSV curves of the ORR / OER dual-functional performance of the FePc / NiFe-LDH@CB micro-nanocomposite material prepared in Example 3 and Pt / C+RuO2.
[0027] Fig.13 This is an open circuit voltage performance diagram of the bifunctional oxygen electrocatalyst prepared in Example 3 of the present invention used in a liquid zinc-air battery.
[0028] Fig.14 This is a discharge polarization curve of the bifunctional oxygen electrocatalyst prepared in Example 3 of the present invention used in a liquid zinc-air battery.
[0029] Fig.15 This is a test chart of the charge and discharge cycle stability of the bifunctional oxygen electrocatalyst prepared in Example 3 for liquid zinc-air batteries. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] Example 1 (1) Preparation of NiFe-LDH@CB Carbon black was dispersed in deionized water to form a suspension with a concentration of 2.5 g / L. Nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and iron nitrate nonahydrate (Fe(NO3)3·9H2O) were dissolved in the suspension with concentrations of 0.15-0.3 g / L and 0.05-0.1 g / L, respectively. Excess potassium hydroxide solution was mixed with the suspension, aged at room temperature for 50-80 min, washed by centrifugation several times, and dried for 12 hours to obtain NiFe-LDH@CB.
[0035] Example 2 (1) Preparation of FePc@CB Carbon black was dispersed in DMF to form a suspension with a concentration of 2.5 g / L. FePc was dissolved in the suspension with a concentration of 0.5-0.8 g / L. After stirring overnight, the suspension was centrifuged and washed with DMF and dried to obtain FePc@CB.
[0036] Example 3 (1) Preparation of NiFe-LDH@CB Carbon black was dispersed in deionized water to form a suspension with a concentration of 2.5 g / L. Nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and iron nitrate nonahydrate (Fe(NO3)3·9H2O) were dissolved in the suspension with concentrations of 0.15-0.3 g / L and 0.05-0.1 g / L, respectively. Excess potassium hydroxide solution was mixed with the suspension, aged at room temperature for 50-80 min, washed by centrifugation several times, and dried for 12 hours to obtain NiFe-LDH@CB.
[0037] (2) Preparation of FePc / NiFe-LDH@CB Disperse NiFe-LDH @CB in DMF to form a suspension. Dissolve FePc in the suspension at a concentration of 0.6 g / L. Stir overnight and centrifuge and wash with DMF to dry to obtain FePc / NiFe-LDH @CB.
[0038] The prepared bifunctional oxygen electrocatalyst was subjected to scanning electron microscopy analysis, X-ray diffraction analysis, X-ray photoelectron spectroscopy analysis, Fourier transform infrared spectroscopy analysis, ORR, OER, ORR stability test, liquid zinc-air battery open circuit voltage test, liquid zinc-air battery discharge polarization performance test, liquid zinc-air battery charge and discharge cycle stability test, and the results are as follows: Figure 1-Figure 15 shown.
[0039] Figure 1 (SEM image of carbon black substrate) Shows the surface features of the carbon black substrate, showing a uniform particle structure. Such substrates are often used to enhance the performance of subsequent materials, providing good conductivity and support. Figure 2 (SEM image of NiFe-LDH@CB) and Figure 3 (SEM image of FePc@CB) shows that the composite behavior of NiFe-LDH and FePc with carbon black does not change its morphological characteristics. Figure 4 (SEM image of FePc / NiFe-LDH@CB) shows that the morphological characteristics of FePc and NiFe-LDH composited on the carbon black substrate do not change significantly, which may be due to the small size of NiFe-LDH and FePc. Figure 5 In the XRD spectrum of , characteristic diffraction peaks related to NiFe-LDH and carbon black (CB) were observed. The presence of NiFe-LDH was confirmed by comparing the specific peak position and intensity with the standard literature values. The characteristic diffraction peaks of FePc were not detected, probably due to its low content. Figure 6 The FT-IR graph of FePc@CB shows that the characteristic absorption peak of FePc appears, proving the successful loading of FePc on CB. Similarly, the curve of NiFe-LDH@CB also shows the characteristic absorption peak of NiFe-LDH, proving that it was successfully synthesized and loaded on the conductive carbon support. The FT-IR curve of FePc / NiFe-LDH@CB is similar to that of NiFe-LDH@CB, and the characteristic absorption peak of FePc was not detected, which may be due to its low content. Through the analysis results of XRD and FT-IR, it can be confirmed that FePc / NiFe-LDH@CB has been successfully prepared.
[0040] Figure 7 It shows that the Fe-N binding energy in FePc@CB moves toward the high binding energy direction compared with FePc / NiFe-LDH; Figure 8 It is shown that the Ni 2p 3 / 2 The binding energy moves toward the lower binding energy compared to FePc / NiFe-LDH, indicating that electrons flow from FePc to NiFe-LDH and there is obvious charge migration between the two, which helps to improve the bifunctional catalytic activity of the composite material.
[0041] Fig. 9 It shows that the FePc / NiFe-LDH@CB prepared in Example 3 has an excellent half-wave potential (0.925 V), which is higher than FePc@CB (0.916 V) and Pt / C (0.88 V). Fig.10It is shown that the bifunctional catalyst FePc / NiFe-LDH@CB also exhibits good oxygen evolution reaction (OER) activity (E 10 =278 mV), which is better than NiFe-LDH@CB (303 mV) and RuO2 (334 mV).
[0042] Fig.11 and Fig.12 The oxygen reduction reaction (ORR) stability of Example 3 was further tested. After 7200 seconds of chronoamperometry testing, the current retention rate reached 94%, and the LSV decay before and after the oxygen reduction reaction was significantly smaller than that of Pt / C. Fig.13 It shows that the bifunctional activity of FePc / NiFe-LDH@CB composite material (ΔE=0.622 V) is significantly better than that of Pt / C+RuO2 (ΔE=0.72 V).
[0043] Figure 14-15 The results show that after the bifunctional oxygen electrocatalyst prepared in Example 3 is used as the positive electrode material to assemble a liquid zinc-air battery, the open circuit voltage is 1.45 V and the peak power density can reach 202 mW / cm 2 , the assembled liquid zinc-air battery operated stably for more than 2,000 hours.
[0044] Example 4 The method and steps are the same as those in Example 3, except that the amount of FePc used is 0.4 g / L and its half-wave potential is 0.89V.
[0045] Example 5 The method and steps are the same as those in Example 3, except that the amount of FePc used is 0.8 g / L. Its half-wave potential is 0.92 V, which is equivalent to the ORR activity of the sample in Example 3, but the current density is slightly reduced. Example 6 The method and steps are the same as those in Example 3, except that the amount of FePc used is 1.0 g / L. The half-wave potential is 0.91 V, which is slightly lower than that of the sample in Example 3 in terms of ORR activity, and the current density is slightly and significantly reduced.
[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing a FePc / NiFe-LDH@CB composite material, characterized in that: The following steps are involved: (a) Preparation of NiFe-LDH@CB nanospheres: nickel salt and iron salt are added to an aqueous solution containing carbon black, and the mixture is aged in a mixed solution consisting of potassium hydroxide or sodium hydroxide aqueous solution, and then centrifuged, washed and dried to obtain NiFe-LDH@CB nanospheres; (b) Preparation of FePc / NiFe-LDH@CB composite material: NiFe-LDH@CB nanospheres were ultrasonically dispersed in DMF solution, and then FePc was dispersed in the solution. The mixture was stirred overnight, and the FePc / NiFe-LDH@CB composite material was obtained after centrifugal washing and drying.
2. The method for preparing the FePc / NiFe-LDH@CB composite material according to claim 1, characterized in that: In the step (1), the nickel salt is any one of nickel nitrate, nickel chloride, nickel acetate, and nickel sulfate; the concentration of the nickel salt in the aqueous solution is 0.15-0.3 g / L; the iron salt is any one of iron nitrate, iron chloride, iron acetate, and iron sulfate; the concentration of the iron salt in the aqueous solution is 0.05-0.1 g / L; The concentration of carbon black in the mixed solution is 2.5 g / L, and an excess of sodium hydroxide or potassium hydroxide is added therein.
3. The method for preparing the FePc / NiFe-LDH@CB composite material according to claim 1, characterized in that: In the step (2), the concentration of FePc dispersed in the DMF solution is 0.5-0.8 g / L.
4. The method for preparing the FePc / NiFe-LDH@CB composite material according to claim 1, characterized in that: In the step (2), the NiFe-LDH@CB nanospheres are placed in a DMF solution and ultrasonically dispersed for 20-50 minutes.
5. The FePc / NiFe-LDH@CB composite material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: FePc and NiFe-LDH are composited on carbon black CB.
6. A liquid zinc-air battery, characterized in that: The FePc / NiFe-LDH@CB micro-nano composite carbon material prepared by the preparation method according to any one of claims 1 to 4 is assembled as the air cathode side.